2004
DOI: 10.2511/rpsd.29.4.218
|View full text |Cite
|
Sign up to set email alerts
|

Caught in the Continuum: A Critical Analysis of the Principle of the Least Restrictive Environment

Abstract: This article presents a critical analysis of the principle of the least restrictive environment (LRE). The article begins with a review of the origins of LRE in professional writings and law and moves next to a discussion of how LRE has been operationalized in terms of a continuum of residential, educational, and vocational services. Building on previous critiques of the continuum concept, the author presents seven conceptual and philosophical flaws or pitfalls in the LRE principle itself, especially when it i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
72
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(72 citation statements)
references
References 12 publications
0
72
0
Order By: Relevance
“…If we regard them as a series of individual threads, do we not increase the chance that our focus opens up gaps between them through which people will continue to fall or through which people fear to fall? As Taylor (1988) suggested, new continua are open to similar critiques as the old continua. They become 'options' within bureaucracies administering and funding services.…”
Section: Continuum Reviewmentioning
confidence: 99%
“…If we regard them as a series of individual threads, do we not increase the chance that our focus opens up gaps between them through which people will continue to fall or through which people fear to fall? As Taylor (1988) suggested, new continua are open to similar critiques as the old continua. They become 'options' within bureaucracies administering and funding services.…”
Section: Continuum Reviewmentioning
confidence: 99%
“…Prior to beginning the data extraction the research team identified six papers (Booth, 1994;Fuchs, Fuchs, & Stecker, 2010;Nisbet, 2004;Norwich, 2008;Taylor, 1988;Taylor, 2001) which could serve as a baseline for our discussion of the conceptualisation of the continuum. These papers were identified by each pair of reviewers following stage 1 screening.…”
Section: Identifying and Describing Sources For The Literature Reviewmentioning
confidence: 99%
“…In other instances the arrow represents a shifting emphasis upon an aspect of the provision (e.g. intensity or restrictiveness of provision - Taylor, 1988). In other representations a lack of arrows might be seen to encapsulate a lack of movement and inward looking 'silo' thinking (eg Maryland State Department of Education, 1969).…”
mentioning
confidence: 99%
See 2 more Smart Citations